FUNGI ISOLATED FROM THE EXCRETA OF WILD BIRDS IN SCREENING CENTERS IN PELOTAS, RS, BRAZIL - Mendes, Josiara Furtado; Albano, Ana Paula Neuschrank; Coimbra, Marco Antônio A.; Ferreira, Gracialda Ferreira de; Gonçalves, Carolina Lambrecht; Nascente, Patrícia da Silva; Mello, João Roberto Braga de (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
The identification of the fungal species belonging to the healthy microflora in animals is a precondition for the recognition of pathological processes causing them. The aim of this study was to investigate the presence of potentially pathogenic fungi in the feces of wild birds collected in Screening Centers. Samples were collected from the feces of 50 cages with different species of birds. The samples were processed according to the modified method STAIB and the plates incubated at 32 °C for up to ten days with daily observation for detection of fungal growth. The isolation of the following species was observed: Malassezia pachydermatis, Candida albicans, C. famata, C. guilliermondii, C. sphaerica, C. globosa, C. catenulata, C. ciferri, C. intermedia, Cryptococcus laurentii, Trichosporon asahii, Geotrichum klebahnii, Aspergillus spp., A. niger and Penicillium spp. Knowing the character of some opportunistic fungi is important in identifying them, facilitating the adoption of preventive measures, such as proper cleaning of cages, since the accumulation of excreta may indicate a risk for both health professionals and centers for screening public health.